An old disease, a new diagnosis; A 49 year-old man with nephrotic syndrome - Santiago Cedeño; Ursula Verdalles; Marian Goicoechea; Soledad García de Vinuesa; José Luño (Society of Diabetic Nephropathy Prevention, 2019)
Background: IgG4-related disease (IgG4-RD) is a systemic immune-mediated disease that typically manifests as fibro-inflammatory masses that can affect nearly any organ system. Case Report: We present here a case of a 49-year old man with forgotten old disease (Mikulicz disease) with membranous nephropathy (MN). Conclusions: This entity is currently included within the spectrum of IgG4-related disease. The development of renal disease shortly after the suspension of rituximab suggests another probable pathway involved. To our knowledge the transforming growth factor may be responsible for existing pattern of fibrosis in this disease. The lack of response or at least partial response to rituximab can be explained by greater involvement of regulatory T lymphocyte in the pathophysiology of this entity